Conjugated geometries - Paris, Leonardo (DISEGNARECON, 2012)
The study of the gears is based on the conjugated geometries in which two curves or two surfaces are maintained in constant contact even if in mutual movement. The geometric theory of the gears until the end of the nineteenth century was one of many branches in the applications of descriptive geometry. The study is based on knowledge of the main properties of plane curves and humps and their derivatives. The specificity of the theme is that these geometries when you have to relate with their conjugated, must meet the constraints that would otherwise not have. We want to highlight through case studies the role of descriptive geometry in the transition from the theoretical to the practical reinventing key information, issues and procedures of investigation often passed into the background if not forgotten.